2020
DOI: 10.1016/j.brs.2020.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus frequency modulates brainstem response to respiratory-gated transcutaneous auricular vagus nerve stimulation

Abstract: a b s t r a c tBackground: The therapeutic potential of transcutaneous auricular VNS (taVNS) is currently being explored for numerous clinical applications. However, optimized response for different clinical indications may depend on specific neuromodulation parameters, and systematic assessments of their influence are still needed to optimize this promising approach. Hypothesis: We proposed that stimulation frequency would have a significant effect on nucleus tractus solitarii (NTS) functional MRI (fMRI) resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
64
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 48 publications
(49 reference statements)
9
64
0
4
Order By: Relevance
“…As expected, locus coeruleus activation was reported in five out of the seven studies (81-83, 85, 86). Three studies showed an activation of the raphe nuclei following taVNS, either contralateral to the stimulation (82) or bilaterally (85,86), while Badran et al reported no difference (84). Altogether, the studies that analyzed the brainstem with an appropriate protocol (82,83,85,86) supported the activation of the lower and upper brainstem, thereby confirming our hypotheses.…”
Section: Hypothesis Challengesupporting
confidence: 84%
See 4 more Smart Citations
“…As expected, locus coeruleus activation was reported in five out of the seven studies (81-83, 85, 86). Three studies showed an activation of the raphe nuclei following taVNS, either contralateral to the stimulation (82) or bilaterally (85,86), while Badran et al reported no difference (84). Altogether, the studies that analyzed the brainstem with an appropriate protocol (82,83,85,86) supported the activation of the lower and upper brainstem, thereby confirming our hypotheses.…”
Section: Hypothesis Challengesupporting
confidence: 84%
“…Stimulation delivered at 100 Hz resulted in a significant increase in the fMRI signal in all targeted brainstem nuclei (ipsilateral periaqueductal and ambiguous nuclei in addition to the nuclei described in the Table 1) compared to no stimulation. Significant differences were also reported at 2 Hz, but only in the dorsal raphe and the contralateral locus coeruleus (86).…”
Section: Studies In Healthy Controlsmentioning
confidence: 85%
See 3 more Smart Citations